Quality measures of two-stage newborn hearing screening: systematic review and meta-analysis - Manz, Kirsi; Nennstiel, Uta; Marzi, Carola; Mansmann, Ulrich; Brockow, Inken (Frontiers in Public Health, 2025)
IntroductionNewborn screening for hearing impairment (NHS) is a crucial public health issue worldwide. Often, a two-stage screening with two different testing approaches is used. We aimed to investigate the optimal screening algorithm, based on data from the literature published in the last 30 years. A particular focus of the study was to synthesize the existing evidence on two-stage newborn hearing screening regarding the refer rate (RFR), the percentage of children that did not pass the second test or were lost after the first test.MethodsWe searched MEDLINE and Scopus for studies on two-stage NHS using transient evoked otoacoustic emissions (TEOAE) or automated auditory brainstem response (AABR). All studies on newborns who received their first test as an inpatient and a second test up to 1 month later were eligible. Random effects meta-analysis was performed to estimate RFR. Risk of bias was assessed using QUADAS-II. The unfunded study was registered in PROSPERO (CRD42023403091, available at https://www.crd.york.ac.uk/PROSPERO/view/CRD42023403091).ResultsEighty-five study protocols, including over 1,120,000 newborns, met the inclusion criteria. Certainty in the evidence was rated as moderate.DiscussionStrategies that did not involve changes to the screening method had a lower RFR. AABR-AABR: RFR = 1.3% [95% confidence interval (CI): 0.9, 1.8%], TEOAE-TEOAE: RFR = 2.7% (CI: 2.2, 3.2%), TEOAE-AABR: RFR = 3.9% (CI: 2.9, 5.1%), AABR-TEOAE: 5.9% (CI: 5.0, 6.9%). Consequently, where feasible, changing the screening method at the second screening should be avoided in order to minimize the number of follow-up examinations.